Words in the dust - Reedy, Trent (New York : Arthur A. Levine Books, 2011)
Zulaikha, a thirteen-year-old girl in Afghanistan, faces a series of frightening but exhilarating changes in her life as she defies her father and secretly meets with an old woman who teaches her to read, her older sister gets married, and American troops offer her surgery to fix her disfiguring cleft lip.
Publisher's Weekly, November 2010
Kirkus Review, December 2010
Includes bibliographical references (p. 263-264).
4.8
5-8
Keywords: Families -- Afghanistan -- Juvenile fiction; Cleft lip -- Juvenile fiction; Sex role -- Juvenile fiction; Literacy -- Juvenile fiction; Afghanistan -- Juvenile fiction; Family life -- Fiction; Cleft lip -- Fiction; Sex role -- Fiction; Literacy -- Fiction; Afghanistan -- Fiction; Family life -- Afghanistan -- Fiction; Cleft lip -- Fiction; Sex role -- Fiction; Literacy -- Fiction; Afghanistan -- Fiction